The Interaction of Metaphor and Metonymy in the Interpretation of Persian Complex Verbs Containing Loanwords - Fatemeh Bahrami (Literary Arts)
Metaphor and metonymy are applied routinely as ongoing linguistic phenomena in meaning extension. The present study, paying attention to Persian complex verbs, i.e. compound and phrasal verbs containing loanwords, examined the metonymic and metaphoric meaning shifts of the loanwords in Persian light verbs. Evidence is mainly extracted from the Persian Dictionary of Secret Words and is analyzed based on the cognitive model proposed by Ruiz de Mendoza and Galera-Masegosa (2011). The results showed the independence of metonymic processes and the dependence of metaphors on the metonymic shifts. It was also found that the processes involved in Persian are far more complicated. A total of twelve patterns were categorized, eight of which were unique to Persian. Among these, three patterns were based solely on metonymy and others were obtained from the interaction of metaphor and metonymy, namely: metonymic expansion of the metaphoric domain, metonymic reduction of the metaphoric domain, a successive chain of expansion and reduction of the domain, metonymic expansion of the source domain and metonymic reduction of the target domain, metonymic reduction of source domain and metonymic expansion of target domain, double reduction of source and target domain, metaphoric amalgams of two target domains in a single source domain, and metaphoric chain with metonymic reduction of the first source domain. The other four patterns corresponded to ones proposed by de Mendoza and Galera-Masegosa (i.e. metaphoric expansion of source domain, metaphoric reduction of source domain, metaphoric reduction of target domain, and metaphoric amalgams). A total of nineteen patterns were obtained, which shows that human language has a high capability in the interaction of metaphor and metonymy.